2023
DOI: 10.3847/1538-4357/acfb86
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of ∼0.05–2 MeV Ions Associated with the 2022 February 16 Energetic Storm Particle Event Observed by Parker Solar Probe

Joe Giacalone,
C. M. S. Cohen,
D. J. McComas
et al.

Abstract: We present analyses of 0.05–2 MeV ions from the 2022 February 16 energetic storm particle event observed by Parker Solar Probe's (PSP) IS⊙IS/EPI-Lo instrument at 0.35 au from the Sun. This event was characterized by an enhancement in ion fluxes from a quiet background, increasing gradually with time with a nearly flat spectrum, rising sharply near the arrival of the coronal mass ejection (CME)–driven shock, becoming nearly a power-law spectrum, then decaying exponentially afterward, with a rate that was indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Furthermore, Temmer & Bothmer (2022) estimated that the sheath density tends to overcome the ejecta density in the heliocentric distance range of 0.09-0.28 au, after which expansion of the driver generally weakens. We also note that Giacalone et al (2023) came to the same conclusion (i.e., that the 2022 February 15 CME was overexpanding by the time it impacted Parker) by observing the intensity of energetic particle increase behind the shock, possibly resulting from ions filling an expanding volume associated with the propagation of a blast wave.…”
Section: Sheath Regionmentioning
confidence: 53%
See 1 more Smart Citation
“…Furthermore, Temmer & Bothmer (2022) estimated that the sheath density tends to overcome the ejecta density in the heliocentric distance range of 0.09-0.28 au, after which expansion of the driver generally weakens. We also note that Giacalone et al (2023) came to the same conclusion (i.e., that the 2022 February 15 CME was overexpanding by the time it impacted Parker) by observing the intensity of energetic particle increase behind the shock, possibly resulting from ions filling an expanding volume associated with the propagation of a blast wave.…”
Section: Sheath Regionmentioning
confidence: 53%
“…First of all, we note that the abrupt magnetic field jump that we had identified as the CME-driven shock in Section 3.1 (vertical gray line in Figure 5) is indeed accompanied by a prominent rise in the solar wind bulk speed (from ∼550 to ∼850 km s −1 ), a moderate climb in the electron density and temperature, as well as an intensification of suprathermal electron fluxes (the electron flux enhancements observed prior to the shock arrival are due to the strong particle event associated with this eruption analyzed by, e.g., Giacalone et al 2023;Khoo et al 2024). The following sheath region is characterized by highly fluctuating magnetic fields, almostconstant speeds, a declining temperature profile, and a plateauing density trend except for a high-density feature close to its trailing portion.…”
Section: Magnetic Field and Plasma Measurements At Parkermentioning
confidence: 87%
“…Both spacecraft observed energetic protons and electrons soon after the radio burst observation at PSP and later measured a peak enhancement of energetic protons at the shock arrival, suggesting a locally shock-accelerated proton population. A detailed analysis of the ESP event, including the source of the accelerated particles, is available in Giacalone et al (2023; see also Fraschetti & Goldberg 2023). In addition, we also noted an interesting three-slope energy spectrum near the shock, and a more involved investigation is ongoing to characterize the evolution of the energy spectrum during this event.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…The ESP events observed by PSP were limited to lower-energy particles (<1 MeV; Figure 3(f)). Giacalone et al (2023) provide a detailed investigation of the ESP events observed by PSP during this event. It is important to note that the energy widths of these three proton channels are not the same for both spacecraft, and this difference is to be taken into account for cross-calibration in Appendix D. Notably, we observed the presence of an interesting three-slope spectrum with a plateau between 8 and 12 MeV near the shock (not shown here).…”
Section: Observations By Bepicolombo and Parker Solar Probementioning
confidence: 99%
“…On the other hand, κ ∥ from test particle simulations has shown a agreement with the predictions of QLT as noted above. Furthermore, our recent study (Giacalone et al 2023) highlights that QLT a relatively accurate estimation for κ ∥ near the CME-driven shocks. These suggest that the current work can also be helpful to the studies of SEP transport in the solar wind as well as acceleration at the interplanetary shocks.…”
Section: Resultsmentioning
confidence: 85%